The modernization of the Western world : a society transformed - McGrath, John T., 1956-; Martin, Kathleen Callanan, 1949- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2017)
"Presents an overview of the history of Western civilization from ancient history to the current era of globalization"--
The modernization of the Western world / John McGrath and Jay P. Corrin -- Modernization and social change / Kathleen Callanan Martin -- The ancient and classical inheritance / John McGrath -- Europe in the Medieval era / John McGrath -- The late Middle Ages and the transformation of Medieval society / John McGrath -- The Italian Renaissance / John McGrath and Kathleen Callanan Martin -- The Reformation / Susan Hagood Lee -- Commerce, cities, and capitalism / John McGrath -- The centralization and rationalization of the political state / John McGrath -- The Enlightenment / John McGrath -- The French Revolution / John McGrath -- The Industrial Revolution / John W. Mackey -- Classical liberalism and the bourgeois state / Kathleen Callanan Martin -- Karl Marx and the socialist response to capitalism / Kathleen Callanan Martin -- Nationalism and nations / John W. Mackey -- The age of empire / John W. Mackey -- The Great War / Benjamin E. Varat -- Europe between wars / Jay P. Corrin -- The rise of fascism / Jay P. Corrin -- Total war: World War II / Michael G. Kort -- The cold war / Benjamin E. Varat -- Globalization and social change / John McGrath -- Terror and terrorism / John McGrath.
Includes bibliographical references and index.
ENH
Trim Education
Keywords: Social change -- Europe -- History; Social change -- Western countries -- History; Civilization, Modern; Civilization, Western; English language; Europe -- Social conditions; Europe -- History; Western countries -- Social conditions; Western countries -- History